Improving the Accuracy of Financial Reports with the Right Accounting System - Wendy, Wendy (Dhana, 2024)
This study aims to explore how the implementation of the right accounting system can improve the accuracy of financial reports at PT. Wirakarya Sakti. The research method used is a qualitative approach with an exploratory purpose, which focuses on understanding the context and dynamics that exist in the company and the perceptions of related parties in the accounting process. The main data sources come from in-depth interviews with financial managers, accountants, and accounting staff, as well as analysis of company documents such as financial reports, accounting policies, and systems implemented. Participatory observation was also conducted to identify potential problems in ongoing accounting practices. The results of the study indicate that the implementation of a software-based accounting system at PT. Wirakarya Sakti has succeeded in improving the accuracy of financial reports by reducing human error, accelerating the process of data verification and reconciliation, and producing more timely and reliable reports. This system helps in managing transactions in a more structured and efficient manner, and minimizing discrepancies between documents. Thus, this study provides recommendations to continue optimizing the implementation of a technology-based accounting system to support more accurate and efficient financial report management.